2021
DOI: 10.1111/1744-9987.13767
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 lockdown on mood status: A comparison of hemodialysis and oncology patients

Abstract: Introduction Coronavirus related lockdown measures had a severe psychological toll. We investigated the effects of population‐wide infection control measures on hemodialysis (HD) and oncology patients' mood statuses. Methods An electronic survey was used to collect data. We used the Profile of Mood States (POMS) and the Hospital Anxiety and Depression Scale (HADS) to measure the mood statuses. Results The study groups composed of 400 HD, 234 oncology patients, and 276 controls. HADS anxiety and total POMS scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
(21 reference statements)
3
3
0
Order By: Relevance
“…Similar to the findings from previous studies performed on patients with chronic diseases, we also found that FD patients have psychological resilience to the effect of lockdown measures [ 6 8 ]. Negative psychological effects of lockdown measures and social distancing have been well documented [ 6 8 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to the findings from previous studies performed on patients with chronic diseases, we also found that FD patients have psychological resilience to the effect of lockdown measures [ 6 8 ]. Negative psychological effects of lockdown measures and social distancing have been well documented [ 6 8 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the findings from previous studies performed on patients with chronic diseases, we also found that FD patients have psychological resilience to the effect of lockdown measures [ 6 8 ]. Negative psychological effects of lockdown measures and social distancing have been well documented [ 6 8 , 17 ]. Posttraumatic growth along with familiarity with medical issues were suggested as major factors explaining the psychological resilience that we observed in FD patients [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…During the pandemic, the care of cancer patients, the recurrence and progression of cancer due to the postponement of treatment, and the difficulty of accessing the hospital may increase the anxiety of patients more [28][29][30]. On the other hand, dialysis patients go to the hospital more frequently for HD treatment, they were informed more frequently and more personal protective measures were taken, so their trait anxiety levels may decrease [31].…”
Section: Related Factors For the Changes In Stai And Bai Scoresmentioning
confidence: 99%